2021
DOI: 10.15408/jkv.v7i2.22267
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methylene Blue and Methyl Orange by Y-PTC Metal-Organic Framework

Abstract: The yttrium based metal-organic framework (MOF) Y-PTC was synthesized by the solvothermal method using perylene as the linker and yttrium as metal ion. This study aims to assess the photocatalytic activity of yttrium-perylenetetracarboxylate (Y-PTC) metal-organic framework (MOF) toward methylene blue and methyl orange under visible light irradiation. The results of the FTIR analysis showed that Y-PTC MOF had a different structure and composition from its precursor (Na4PTC). The Y-PTC MOF has a bandgap energy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…At 2500-3300 cm -1 in the IR spectrum of Na4PTC, no absorbance band was found for the -OH group. It confirmed that PTCDA reacts completely with four equivalents of NaOH to form Na4PTC (Adawiah et al, 2021).…”
Section: Methylene Blue Elimination Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…At 2500-3300 cm -1 in the IR spectrum of Na4PTC, no absorbance band was found for the -OH group. It confirmed that PTCDA reacts completely with four equivalents of NaOH to form Na4PTC (Adawiah et al, 2021).…”
Section: Methylene Blue Elimination Analysismentioning
confidence: 61%
“…The bands at 1753 and 1730 cm -1 attributed to asymmetric and symmetric stretching vibrations (C=O) of PTCDA 5-member ring cyclic anhydride. The sharp peak at 1234 cm -1 confirmed asymmetric stretching vibration (C-O), and 938 cm -1 identified the symmetric stretching vibration (C-O) of the C-CO-O-CO-C-group in the cyclic anhydride compound of PTCDA (Adawiah et al, 2021). Figure 1 also shows that the five bands of the cyclic anhydride group of the PTCDA no longer appear in the IR spectrum of Na4PTC.…”
Section: Methylene Blue Elimination Analysismentioning
confidence: 91%
“…required by photocatalyst materials for photocatalytic processes [12]. Figure 4 fer much, namely 1.16 Å and 1.01 Å and are in one group [22].…”
Section: Characteristics Of Bimetallic Mofs La-y-ptcmentioning
confidence: 92%
“…Figure 3 shows the pattern of the La-Y-PTC diffractogram in which there are several dif-fraction peaks, including at 2θ = 5.69°, 9.57°, 16.8°; 20.05°; 24.8°, 26.15°; 29.77° and 41.93°. Meanwhile, the diffraction pattern with the highest intensity produced by La-PTC is at 2θ = 6.31º, 16.6º, 28.7º, 33.3º and 44.6º [11], while the diffraction pattern of Y-PTC is at 2θ= 17.04º, 26.27º, and 27.41º [12]. The difference in the absorption peak value indicates the difference in the crystal structure of the MOFs La-Y-PTC.…”
Section: Characteristics Of Bimetallic Mofs La-y-ptcmentioning
confidence: 95%
See 1 more Smart Citation